First Study on Nihonium (Nh, Element 113) Chemistry at TASCA - Yakushev, A.; Lens, L.; Düllmann, Ch. E.; Block, M.; Brand, H.; Calverley, T.; Dasgupta, M.; Di Nitto, A.; Götz, M.; Götz, S.; Haba, H.; Harkness-Brennan, L.; et al. (Frontiers in Chemistry, 2021)
Nihonium (Nh, element 113) and flerovium (Fl, element 114) are the first superheavy elements in which the 7p shell is being filled. A high volatility and inertness were predicted for Fl due to the strong relativistic stabilization of the closed 7p1/2 sub-shell, which originates from a large spin-orbit splitting between the 7p1/2 and 7p3/2 orbitals. One unpaired electron in the outermost 7p1/2 sub-shell in Nh is expected to give rise to a higher chemical reactivity. Theoretical predictions on the Nh reactivity are discussed, along with results of the first experimental attempts to study the Nh chemistry in the gas phase. The experimental observations verify a higher chemical reactivity of Nh atoms compared to its neighbor Fl, and call for the development of advanced setups. First tests of a newly developed detection device miniCOMPACT with highly reactive Fr isotopes assure that effective chemical studies of Nh are within reach.